Multiple roles for four-jointed in planar polarity and limb patterning. - Zeidler, M.P.; Perrimon, N.; Strutt, D.I. (Developmental Biology, 2000)
Insect cuticles have been a model system for the study of planar polarity for many years and a number of genes required for this process have been identified. These genes organise the polarised arrangement of hairs on the legs, wings, thorax, and abdomen of adult Drosophila. It has previously been shown that four-jointed is involved in planar polarity decisions in the eye as well as proximal distal leg and wing development. We now present evidence that four-jointed is expressed in a gradient through the developing wing and show that it is required for planar polarity determination in both the wing and the abdomen. Clones of cells either lacking or ectopically expressing four-jointed cause both autonomous and nonautonomous repolarisation of hairs in these tissues. We propose that the inferred four-jointed expression gradient is important for planar polarity establishment and that local inversions of the gradient by the clones are the probable cause of the observed polarity phenotypes. In addition we observe defects in wing vein development. The subtle phenotypes of mutant flies, and the diverse patterning processes in which it is involved, suggest that four-jointed may act as a modifier of the activity of multiple other signalling factors.